2023
DOI: 10.3390/cancers15082305
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid NGS Analyses of Paired Samples from Bone Marrow and Peripheral Blood Yield Concordant Results: A Prospective Cohort Analysis of the AGMT Study Group

Abstract: Background: Next generation sequencing (NGS) has become indispensable for diagnosis, risk stratification, prognostication, and monitoring of response in patients with myeloid neoplasias. Guidelines require bone marrow evaluations for the above, which are often not performed outside of clinical trials, indicating a need for surrogate samples. Methods: Myeloid NGS analyses (40 genes and 29 fusion drivers) of 240 consecutive, non-selected, prospectively collected, paired bone marrow/peripheral blood samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…OGT improves ASXL1 stability by inducing O -GlcNAcylation at the ASXL1 Ser199 site [ 127 ], while ASXL1 interacts with and activates BAP1 [ 66 ]. It is reported that ASXL1 is mutated in numerous myeloid malignancies, including MDS, AML, and CMML [ 128 , 129 ], and ASXL1 mutations have been shown to be positively associated with poor prognosis in patients with MDS and AML [ 130 , 131 ]. The ASXL1 mutation occurs at the C-terminus, generating a C-terminally truncated ASXL1 mutant [ 132 , 133 ], which retains the DEUBAD binding domain and facilitated the catalytic activity of BAP1 and promotes H2AK119ub1 deubiquitination, which in turn drives myeloid leukemogenesis [ 134 ].…”
Section: Pr-dub Complexmentioning
confidence: 99%
“…OGT improves ASXL1 stability by inducing O -GlcNAcylation at the ASXL1 Ser199 site [ 127 ], while ASXL1 interacts with and activates BAP1 [ 66 ]. It is reported that ASXL1 is mutated in numerous myeloid malignancies, including MDS, AML, and CMML [ 128 , 129 ], and ASXL1 mutations have been shown to be positively associated with poor prognosis in patients with MDS and AML [ 130 , 131 ]. The ASXL1 mutation occurs at the C-terminus, generating a C-terminally truncated ASXL1 mutant [ 132 , 133 ], which retains the DEUBAD binding domain and facilitated the catalytic activity of BAP1 and promotes H2AK119ub1 deubiquitination, which in turn drives myeloid leukemogenesis [ 134 ].…”
Section: Pr-dub Complexmentioning
confidence: 99%
“…Like others, we note high concordance between PB and BM mutation VAF. 5 , 18 , 19 In principle, PB collections can occur more often, allowing for a more granular analysis of response kinetics than BM. Also, PB avoids complications with hemodilute aspirates and collections are less likely to be declined or missed.…”
mentioning
confidence: 99%